2006
DOI: 10.1073/pnas.0600923103
|View full text |Cite
|
Sign up to set email alerts
|

Whirlin complexes with p55 at the stereocilia tip during hair cell development

Abstract: Hearing in mammals depends upon the proper development of actin-filled stereocilia at the hair cell surface in the inner ear. Whirlin, a PDZ domain-containing protein, is expressed at stereocilia tips and, by virtue of mutations in the whirlin gene, is known to play a key role in stereocilia development. We show that whirlin interacts with the membrane-associated guanylate kinase (MAGUK) protein, erythrocyte protein p55 (p55). p55 is expressed in outer hair cells in long stereocilia that make up the stereocili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 27 publications
3
68
0
Order By: Relevance
“…A link between CLRN1 and Usher II gene products can be established through the interaction of CLRN1 with protein 4.1. Protein 4.1 binds indirectly to whirlin, an Usher type IID protein, along with the membrane-associated MAGUS family protein, p55 (53). Our studies support and extend the previously proposed hypothesis that Usher proteins interact together to form an intricate network wherein deficiencies can lead to similar disease phenotypes of variable severity (reviewed in Refs.…”
Section: Discussionsupporting
confidence: 78%
“…A link between CLRN1 and Usher II gene products can be established through the interaction of CLRN1 with protein 4.1. Protein 4.1 binds indirectly to whirlin, an Usher type IID protein, along with the membrane-associated MAGUS family protein, p55 (53). Our studies support and extend the previously proposed hypothesis that Usher proteins interact together to form an intricate network wherein deficiencies can lead to similar disease phenotypes of variable severity (reviewed in Refs.…”
Section: Discussionsupporting
confidence: 78%
“…MAGUKs, including the Drosophila Dlg tumor suppressor, function as regulators of cell polarity (26). Recent findings have shown that p55 forms a complex with whirlin and regulates cell polarity during hair cell development (27). Mutations in the whirlin gene cause deafness and Usher syndrome, and p55 also interacts with MPP5 to link the Usher protein network with the Crumbs protein complex in the retina (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests the membrane-associated guanylate kinase (MAGUK) protein, p55 and protein 4.1R also interact with whirlin and may together form a complex responsible for mediating actin polymerisation and stereocilia development (Mburu et al, 2006). The PDZ1 domain of whirlin can also interact with the cytoplasmic tails of usherin and Vlgr1, both of which contain a C-terminal class I PBM and it has been suggested that whirlin may be involved in the anchoring of the ankle links through its associations with usherin and Vlgr1 and also with myosin VIIa Adato et al, 2005b;Kremer et al, 2006).…”
Section: Pdz-domain and Pdz-domain-binding Proteinsmentioning
confidence: 99%